2021
DOI: 10.3390/su13095252
|View full text |Cite
|
Sign up to set email alerts
|

What Affects the E-Bicycle Speed Perception in the Era of Eco-Sustainable Mobility: A Driving Simulator Study

Abstract: The increase in the number of electric bicycles worldwide has resulted in a rise in the number of traffic accidents involving e-bicyclists. Previous studies have been based on analyzing the use, advantages and disadvantages of e-bicycles, whereas only a small number of studies have been focused on analyzing the e-bicycle traffic safety, particularly the factors leading to the occurrence of traffic accidents. One of the factors affecting the occurrence of traffic accidents is the incorrect perception of the e-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
0
16
0
4
Order By: Relevance
“…This construct is typically suitable for the context of this research since older persons always place significant emphasis on safety issues [5]. Additionally, some recent evidence have reported that riding electric vehicles like an electric bicycle would be a healthrisk behavior because of this mode's silent operation and lighter body [37].…”
Section: External Factors: Descriptive Norms and Perceived Crash Riskmentioning
confidence: 99%
“…This construct is typically suitable for the context of this research since older persons always place significant emphasis on safety issues [5]. Additionally, some recent evidence have reported that riding electric vehicles like an electric bicycle would be a healthrisk behavior because of this mode's silent operation and lighter body [37].…”
Section: External Factors: Descriptive Norms and Perceived Crash Riskmentioning
confidence: 99%
“…Број е-бицикала у саобраћају, како у Свету, тако и у земљама Југоисточне Европе, се повећава (Simović et al, 2021 Због пандемије COVID-19, употреба (е-)бицикала на овој територији постаје све популарнија. Чак 9% испитаника који нису користили бицикл, пре пандемије COVID-19, имају жељу и намеру да пређу на употребу (е-) бицикла (Ivanišević et al, 2021).…”
Section: уводunclassified
“…До погрешне перцепције брзине долази због тога што већина е-бицикала, на европском тржишту, изгледа исто као и традиционални бицикли, па учесници у саобраћају имају погрешна очекивања брзине кретања е-бицикала (Simović et al, 2021). Такође, до погрешне перцепције брзине од стране учесника у саобраћају може доћи у ситуацијама када возач ебицикла прилази другим учесницима у саобраћају са на изглед малим физичким напором, али релативно великим брзинама (Simović et al, 2021)…”
Section: уводunclassified
“…At present, two-wheeled vehicle accidents account for 28% of world traffic fatalities and make up 20% of all traffic deaths in China [ 1 ]. In recent years, study of the perception and protective equipment of two-wheeled vehicles under complex traffic conditions has also received increasing attention from researchers [ 2 , 3 , 4 ]. Qin [ 5 ] made a statistical analysis of 297 two-wheeled vehicle accidents recorded by Shanghai Traffic Police Corps, and the statistical data are shown in Appendix A .…”
Section: Introductionmentioning
confidence: 99%